2015
DOI: 10.1007/s00216-015-8913-x
|View full text |Cite
|
Sign up to set email alerts
|

A guiding light: spectroscopy on digital microfluidic devices using in-plane optical fibre waveguides

Abstract: We present a novel method for in-plane digital microfluidic spectroscopy. In this technique, a custom manifold (.stl file available online as ESM) aligns optical fibres with a digital microfluidic device, allowing optical measurements to be made in the plane of the device. Because of the greater width vs thickness of a droplet on-device, the in-plane alignment of this technique allows it to outperform the sensitivity of vertical absorbance measurements on digital microfluidic (DMF) devices by ∼14×. The new sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…One of the fundamental applications of DMF is the implementation of enzymatic reactions. , The protocol typically consists of precise metering of reactants by dispensing droplets from reservoirs and merging and mixing to create a droplet that represents the microreactor. The microreactors on the DMF device have been analyzed using integrated in-line detectors ,, or with offline detectors (e.g., fluorescence-based plate readers). ,, However, most enzymatic assays on DMF are either performed at room temperature or without refilling of reservoirs for dispensing droplets. ,, These corresponding factors give rise to two limitations: (1) prevents the study of most industrial-based and thermoresistant enzymes, which are active at higher temperatures (>25 °C), and (2) prevents the study of different conditions on the device that requires droplets (containing substrate enzyme, or buffer) to be dispensed multiple times. These limitations motivate the development of our world-to-chip for digital microfluidics for the implementation of enzymatic assays that require heating and testing of multiple conditions in parallel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the fundamental applications of DMF is the implementation of enzymatic reactions. , The protocol typically consists of precise metering of reactants by dispensing droplets from reservoirs and merging and mixing to create a droplet that represents the microreactor. The microreactors on the DMF device have been analyzed using integrated in-line detectors ,, or with offline detectors (e.g., fluorescence-based plate readers). ,, However, most enzymatic assays on DMF are either performed at room temperature or without refilling of reservoirs for dispensing droplets. ,, These corresponding factors give rise to two limitations: (1) prevents the study of most industrial-based and thermoresistant enzymes, which are active at higher temperatures (>25 °C), and (2) prevents the study of different conditions on the device that requires droplets (containing substrate enzyme, or buffer) to be dispensed multiple times. These limitations motivate the development of our world-to-chip for digital microfluidics for the implementation of enzymatic assays that require heating and testing of multiple conditions in parallel.…”
Section: Resultsmentioning
confidence: 99%
“…20,45−48 The protocol typically consists of precise metering of reactants by dispensing droplets from reservoirs and merging and mixing to create a droplet that represents the microreactor. The microreactors on the DMF device have been analyzed using integrated in-line detectors 19,49,50 or with offline detectors (e.g., fluorescence-based plate readers). 5,14,51 However, most enzymatic assays on DMF are either performed at room temperature or without refilling of reservoirs for dispensing droplets.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…In addition, the FA signals from the lysates were found to be highly specific to HumRadA-BRC4 fl interactions, potentially paving the way for diagnostic applications from more complex sample matrices (e.g., bodily fluids). 25 The ability to determine precise FA signals in single droplets also provides the basis for coupling detection with library selections in formats in which droplets cocompartmentalize genotype and phenotype. 26 Anisotropy detection would expand the range of assays that can be used for library selections in protein engineering by directed evolution 27 or metagenomic screening, 8c to enable not only assays that lead to production of fluorophores (e.g., as leaving groups 8b ), but also, assays that instead detect size changes by fluorescence anisotropy (e.g., for enzymatic breakdown of macromolecular targets by proteases of glycosidases).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that extracting the two key parameters, K d and level of protein expression, was possible via acquisition of just two high-resolution titrations. In addition, the FA signals from the lysates were found to be highly specific to HumRadA-BRC4 fl interactions, potentially paving the way for diagnostic applications from more complex sample matrices (e.g., bodily fluids) . The ability to determine precise FA signals in single droplets also provides the basis for coupling detection with library selections in formats in which droplets cocompartmentalize genotype and phenotype .…”
Section: Discussionmentioning
confidence: 99%
“…To address this bottleneck, there has been tremendous progress in recent years in integrating droplet microfluidics with a number of label-free analytical measurements. ,,, , Notably, Holland-Moritz et al developed a mass spectrometry-activated droplet sorter that circumvents the sample-destructive nature of mass spectrometry by splitting droplets into two streams, analyzing a portion with electrospray ionization mass spectrometry in real-time, and sorting the partner droplet stream based on the mass spectra. While a very promising approach, its overall throughput of 0.7 samples per second leaves much to be desired for high-throughput screens.…”
mentioning
confidence: 99%